1988
DOI: 10.3164/jcbn.5.43
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Response to D-Glucosone in Terms of Motility of the Stomach, Insulin Secretion, and Sweetness

Abstract: D-Glucosone (D-arabino-hexos-2-ulose) was prepared by use of an immobilized glucose 2-oxidase-catalase gel, and the biochemical response to D-glucosone by three kinds of glucose-recognizing systems in higher animals was studied. The enhanced motility of rat stomach caused by glucopenia was reduced by carotid arterial injection of D-glucosone like in the case of D-glucose. D-Glucosone (16.7 mM) showed no effect on the secretion of insulin from the pancreatic islets of the rat, and the secretion of insulin cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
1990
1990

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Pyranose oxidase, a flavoprotein with an assumed mechanism similar to glucose oxidase, has only twice been described for analytical use and then with soluble enzyme (15,16). In a recent study we demonstrated the immobilization of this enzyme with results of significant increased stability at higher temperature and prolongation of operational and storage life (11).…”
Section: Resultsmentioning
confidence: 99%
“…Pyranose oxidase, a flavoprotein with an assumed mechanism similar to glucose oxidase, has only twice been described for analytical use and then with soluble enzyme (15,16). In a recent study we demonstrated the immobilization of this enzyme with results of significant increased stability at higher temperature and prolongation of operational and storage life (11).…”
Section: Resultsmentioning
confidence: 99%